Nutrient requirements of goats : Angora, dairy, and meat goats in temperate and tropical countries / Subcommittee on Goat Nutrition, Committee on Animal Nutrition, Board on Agriculture and Renewable Resources, Commission on Natural Resources, National Research Council. (1981)
Summary goes here